The Phenomenon of Scroll, Checkout, Repeat from the Perspective of Hadith: A Thematic Study of the Concept of Israf and Consumption Control - Mohammad Yusuf Zakaria; Vivin Nurfaida; Muhid Muhid (MASI Mandiri Edukasi, 2026)
The rapid growth of e-commerce has transformed modern consumption patterns into increasingly instant, spontaneous, and repetitive behaviors, a phenomenon aptly described as